Curriculum Innovation And Instructional Design For Future Oriented Education Systems - Luka Novak (J-PE: Jurnal Pendidikan, 2026)
Education systems are undergoing rapid transformation influenced by technological advancement, global connectivity, and shifting societal expectations. Traditional curriculum structures centered on knowledge transmission no longer fully address the competencies required in contemporary societies. This article examines the relationship between curriculum innovation and instructional design in shaping future oriented education systems. A qualitative literature based approach was employed through the analysis of scholarly articles, policy reports, and theoretical frameworks related to curriculum reform, digital pedagogy, and learner centered education. The review identifies several principles that characterize contemporary curriculum innovation, including competency based learning, interdisciplinary integration, learner agency, and technology enhanced learning environments. Instructional design functions as a mediating mechanism that translates curriculum vision into structured learning experiences through project based learning, digital learning environments, and authentic assessment practices. The study highlights that education systems capable of integrating innovative curriculum frameworks with strategic instructional design are better prepared to cultivate adaptable learners who can respond to complex and rapidly changing global contexts.